The roles of formal and informal institutions on innovations activity - Lee, Weng Chang; Law, Siong Hook (Penerbit Universiti Kebangsaan Malaysia, 2016)
This paper analyses the impact of institutions on the innovation level of countries. This analysis is performed by segregating the dimension of institution into two, namely formal institutions and informal institutions. Using samples of 62 cross-section countries and employing robust standard error ordinary least squares (OLS) estimation, this study has found evidence that both formal and informal institutions affect the innovation level of countries. The results suggest that countries with higher formal institutions (institutional quality) and higher informal institutions (social capital) are associated with higher innovation levels. However, informal institutions demonstrate that at 10th percentile quantile estimations it exhibit a significant positive impact on innovation, while the formal institutions show such impact after exceeding the 50th percentile. Hence, this result suggests the formal institutions play important role when innovation level in a country is high. Both formal and informal institutions are crucial in influencing the level of country’s innovation.